Comparison of muscle activity of the lower limbs while running on different treadmill models - Kaltenbach, Christina; Gollhofer, Albert; Nigg, Benno M.; Asmussen, Michael J. (Frontiers in Human Neuroscience, 2024)
Running on treadmills is a common method to exercise and to study human locomotion.Research has examined the kinematics and kinetics of overground and treadmill running, but there has been less focus on the levels of muscle activity during treadmill running. We investigated if muscle activity is different while running overground compared to running on a variety of treadmills.11 healthy individuals ran at 3 speeds (2.6, 3.6, 4.5m/s) under 4 different running conditions (3 treadmills, overground). The three treadmills included a typical home exercise treadmill, a midsize commercial research treadmill, and a large, instrumented research treadmill. Surface EMG of the tibialis anterior (TA), gastrocnemius medialis (GM), rectus femoris (RF) and biceps femoris (BF) muscles were measured for each running condition. The integrated EMG was computed for each running condition for the stance and swing phase, as well as 100ms before and after the heel-strike.Friedman analysis revealed significant effects during the stance phase for GM and RF at all speeds, such that muscle activation was lower on the treadmills relative to overground. The muscle activity was higher for the TA and lower for the BF on the treadmills compared to overground at higher speeds during stance phase. Before heel-strike, the TA was significantly less active during treadmill compared to over ground running at 2.6m/s and the RF showed significantly higher activity at 3.6m/s and 4.5m/s while running on the different treadmills.Differences were mainly observed between the different treadmill conditions relative to overground running. Muscle activation differences between the different treadmill conditions were observed at faster running speeds for RF during the pre-heel-strike phase only.Different types of treadmills with different mechanical properties affects the muscle activity during stance phase as well as in preparation to heel-strike. Additionally, the muscle activity is greater during overground compared to treadmill running during the stance phase for the GM, BF and RF.